Answer:
[tex]x=1+\dfrac{3}{1-Ke^{3t}}[/tex]
Step-by-step explanation:
Given that
[tex]\dfrac{dx}{dt}=x^2-5x+4[/tex]
This is a differential equation.
Now by separating variables
[tex]\dfrac{dx}{x^2-5x+4}=dt[/tex]
[tex]\dfrac{dx}{(x-1)(x-4)}=dt[/tex]
[tex]\dfrac{1}{3}\left(\dfrac{1}{x-4}-\dfrac{1}{x-1}\right)dx=dt[/tex]
Now by integrating both side
[tex]\int\dfrac{1}{3}\left(\dfrac{1}{x-4}-\dfrac{1}{x-1}\right)dx=\int dt[/tex]
[tex]\dfrac{1}{3}\left(\ln(x-4)-\ln(x-1)\right )=t+C[/tex]
Where C is the constant
[tex]\dfrac{1}{3}\ln\dfrac{x-4}{x-1}=t+C[/tex]
[tex]\dfrac{x-4}{x-1}=Ke^{3t}[/tex] K is the constant.
[tex]x=1+\dfrac{3}{1-Ke^{3t}}[/tex]
So the solution of above differential equation is
[tex]x=1+\dfrac{3}{1-Ke^{3t}}[/tex]